The Effect of Perfectionism and Test Anxiety on Academic Burnout in High School Students - Lee, Angel; Iskandar, Amirul (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aimed to investigate the effects of perfectionism and test anxiety on academic burnout among high school students in Malaysia. Methods and Materials: A correlational descriptive research design was employed to examine the relationships between perfectionism, test anxiety, and academic burnout. The sample consisted of 400 high school students selected through simple random sampling based on the Krejcie and Morgan table. Standardized instruments were used to measure the study variables, including the Frost Multidimensional Perfectionism Scale (FMPS) for perfectionism, the Test Anxiety Inventory (TAI) for test anxiety, and the Maslach Burnout Inventory–Student Survey (MBI-SS) for academic burnout. Data were analyzed using SPSS-27. Pearson correlation was used to explore the relationships between the dependent variable and each independent variable, and linear regression analysis was conducted to assess the combined predictive power of perfectionism and test anxiety on academic burnout. Findings; The results indicated that both perfectionism and test anxiety had significant positive correlations with academic burnout (p < .01). The linear regression analysis revealed that perfectionism and test anxiety together significantly predicted academic burnout, accounting for a meaningful proportion of the variance in burnout scores (R² = .41, F(2, 397) = 137.6, p < .001). These findings suggest that students with higher levels of perfectionism and test anxiety are more likely to experience emotional exhaustion, cynicism, and reduced academic efficacy. Conclusion: The study highlights the critical role of perfectionism and test anxiety in the development of academic burnout among high school students. Interventions targeting these psychological factors may be essential in promoting academic well-being and preventing burnout in adolescents within high-pressure educational environments.